The Role of Institutions in Output Growth Volatility- Financial Development Nexus: A Worldwide Study (2016)
Purpose – The purpose of this paper is to investigate the role of institutions in the financial development-output growth volatility nexus. It provides new channels through which financial development can dampen the output growth volatilities of the countries under investigation. Design/methodology/approach – A comprehensive data set for 71 countries covering the period from 1996 to 2012 and the System GMM approach were used. The choice of the methodology is to deal with endogeneity issues such as measurement errors, reverse causality among other issues. Findings – A number of findings were emanated from the empirical analysis. First, the estimates provided evidence of the volatility-reducing effect of financial development. Second, institutions do not have the same reducing influence on output growth volatility. Third, the interaction of financial development and institutions showed that the output volatility reduction arising from financial development is enhanced in the presence of improved institutions. Research limitations/implications – The policy implications derived from this study are in twofolds: first, it is important for policymakers to formulate policies that would ensure and enhance the development of the financial sectors, since its importance in minimizing output volatility has been established. Second, institutional quality should be developed so as to further enhance the growth volatility-reducing influence of financial development. Particularly, institutions should be improved along the multiple dimensions captured in the analysis. Originality/value – To the best knowledge, the novelty of this study to the literature is the introduction of institutions, which is hypothesized to increase the dampening effects of financial development in output growth volatility.